Routine screening and rates of metabolic syndrome in patients treated with clozapine and long-acting injectable antipsychotic medications: a cross-sectional study. (24th March 2021) - Lydon, A.; Vallely, J.; Tummon, A.; Maher, S.; Sabri, S.; McLoughlin, J.; Liew, A.; McDonald, C.; Hallahan, B.
Abstract : Objectives: To examine the rate of monitoring of metabolic syndrome and actual rates of metabolic syndrome in two patient cohorts [clozapine treatment and long-acting injectable (LAI) antipsychotic] who are reviewed on an equally regular basis (1–4 weekly) for administration of treatment. Methods: Clinical and laboratory data are examined on 119 patients treated with clozapine and 116 patients treated with LAI antipsychotic medications to determine the rates of metabolic syndrome and evidence of monitoring for metabolic syndrome in the previous 6 months. Individuals with insufficient data from these cohorts were invited to attend for metabolic screening to determine actual rates of metabolic syndrome in these two cohorts of patients. Results: All metabolic parameters were monitored to a significantly greater extent in the clozapine cohort (>90%), compared to those treated with LAI antipsychotic medications (<50%) (blood pressure, weight, lipid and glucose levels; p < 0.001). Metabolic syndrome was present in 38.9% of those treated with clozapine compared to 31.1% of patients treated with LAI antipsychotic medications ( X 2 = 0.54, p = 0.46). Conclusions: These findings suggest that a robust screening plan should be in place to monitor for metabolic syndrome in individuals treated with LAI antipsychotic medications. This screening should include measurement of body weight, waist circumference, fasting glucose, lipids and fasting insulin levels. Early recognition of abnormal metabolic parameters allows early intervention, therefore, improving long-term cardiovascular outcomes.